2022
DOI: 10.3390/su142214891
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Psychometric Properties and Measurement Invariance of the Perceived Motivational Climate in Sport Questionnaire (PMCSQ-2): Online Assessment

Nuria Pérez-Romero,
Rafael E. Reigal,
María Auxiliadora Franquelo
et al.

Abstract: Athletes’ perception of competence and success can be influenced by the motivational climate created by the coach. The Perceived Motivational Climate in Sport Questionnaire (PMCSQ-2) assesses this. Although its reliability and validity have been analyzed in previous studies, this has never been done for the online version. This type of evaluation can be beneficial for data collection, sustainability, speed, and generating larger samples. Therefore, the aim of this study is to analyze the psychometric propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As can be seen, the total for the online version reached a sample size of 5866 for all five studies, while for the paper-and-pencil version, a total of 5628 was reached using eleven studies. Taking into account the five online version studies, a total of 5866 participants were collected: 2320 for the first article [41], 1050 for the second [42], 1637 for the third [43], 705 for the fourth [38], and 154 for the last [39]. This amount was considered in the application of the equation offered by González Ruiz [31], which allows for calculating the percentage of paper savings.…”
Section: Efficiency Of Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen, the total for the online version reached a sample size of 5866 for all five studies, while for the paper-and-pencil version, a total of 5628 was reached using eleven studies. Taking into account the five online version studies, a total of 5866 participants were collected: 2320 for the first article [41], 1050 for the second [42], 1637 for the third [43], 705 for the fourth [38], and 154 for the last [39]. This amount was considered in the application of the equation offered by González Ruiz [31], which allows for calculating the percentage of paper savings.…”
Section: Efficiency Of Sample Collectionmentioning
confidence: 99%
“…Areas that have already been validated include assessments of hypnosis, motivation, and attention. These areas have been shown to hold significance in the context of sports and physical activity [38][39][40][41][42][43]. Regarding the reliability of online tools compared to their paper-based counterparts, the studies by Franquelo et al [38,39], which validated the online version of the Valencia Scale of Attitudes and Beliefs toward Hypnosis (therapist version and client version), found that online measures were equivalent in terms of reliability to paper-based versions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation